Analysis of Aerosol Optical Depth and Angstrom Exponents over an AERONET site at Pokhara, Nepal - Regmi, Jeevan; Poudyal, Khem N; Pokhrel, Amod; Gyawali, Madhu; Barinelli, Anthony; Aryal, Rudra (BIBECHANA, 2021)
The monthly variability of Aerosol Optical Depth at 0.50 μm (AOD0.50) and Ångström exponents (AE) based on spectral AODs over an Aerosol Robotic Network (AERONET) site Pokhara are analyzed by using aerosol data of the year 2017. The AOD0.50 are characterized by low average values (0.21± 0.12) in monsoon, and highest values in pre-monsoon (0.67± 0.14) followed by winter (0.46± 0.28) and post-monsoon (0.33±.02) with an overall mean of 0.43 ± 0.02. The average AE obtained by using AODs at 0.44 μm and 0.87 μm is 1.20± 0.04 in pre-monsoon, 1.37± 0.05 in monsoon, 1.41±.01 in post-monsoon, and 1.37± 0.07 in winter with an annual average value of 1.35 ± 0.08. These overall variations of AE indicate that the majority of aerosol loading during the study period was a mixture of fine and coarse mode aerosols and the influence of anthropogenic aerosols. The monthly average AOD suggests low aerosol loading in the months of the monsoon season (June to September) than other months of pre-monsoon season (March to May) and post-monsoon season (October and November). BIBECHANA 18 (1) (2021) 118-127